Mätning av hästars ättider av grovfoder i en aktiv grupphästhållning - Erikstedt, Sabina; Ronell, Malin (2016)
Measurements in horses of feeding times of haylage in an active open barn system In an active open barn, such as Active Stable®, the ratio of roughage to each horse is controlled by a transponder that regulates the horses time for feeding in certain amount of minutes each day. Recommended feeding-times for these kinds of housing systems are generalized which entails that the horse’s ratio will not be individualized. A measurement of how long it takes for the horse to eat a certain amount of roughage is made to calculate how many minutes the horse needs to get its daily need of roughage. This measurement is needed to be able to create an individual and reliable ration for each horse, also to be able to give recommendations for a feeding-strategy in an active open barn.